Pembuatan Aplikasi Messenger Berbasis Android - Aldi Renaldi Gunawan; Justinus Andjarwirawan; Yulia Yulia (Jurnal Infra, 2016)
The development of information technology is currently growing very rapidly. One of which is how to use messenger application on mobile device. Nowadays, messenger is one of the applications that are used to communicate by most people. This thesis aims to create a messenger application that can communicate between mobile devices especially devices with the Android operating system.In the design and implementation of this application, there is a server side comprising: Openfire server that serves as a protocol in the exchange of messages and the Apache server that serves to accommodate the user data. As well as the client side comprising: user interface display applications. This application provides features such as login, registration, chat, create groups and invite friends or group.From the results of tests on various Android devices with different versions and brands like LG G4 , LG G2 , Samsung Galaxy S2 ,Sony Xperia SP and Sony Xperia Z3 Compact the application run well on all devices. But for the view, the position of the layout as TextView , ImageView , videoview and also listview do not go well because of using density pixel (DP) so the size of each display device which has different pixel per inch (PPI) will show different results.In addition on the device Samsung Galaxy S2 with Android 4.1.2 version popup menu button located on the menu friends is not found.